2021
DOI: 10.1152/japplphysiol.00939.2020
|View full text |Cite
|
Sign up to set email alerts
|

Regional and interindividual relationships between cerebral perfusion and oxygen metabolism

Abstract: Quantitative measurements of resting cerebral blood flow (CBF) and metabolic rate of oxygen (CMRO2) show large between-subject and regional variability, but the relationships between CBF and CMRO2 measurements regionally and globally are not fully established. Here, we investigated the between-subject and regional associations between CBF and CMRO2 measures with independent and quantitative PET techniques. We included resting CBF and CMRO2 measurements from 50 healthy volunteers (aged 22-81 years), and calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 52 publications
(14 reference statements)
5
9
0
Order By: Relevance
“…In contrast, the higher between-region CoV of relative GM CBF averaged across subjects (11.4%) over within-region CoV (2–4%) yielded excellent ICC values of VSASL for detecting normal variations of regional CBF ( Table 3 ). The higher relative CBF values in the occipital lobe (1.05), cerebellum (1.07), and posterior cingulate cortex (1.15) were consistent with the regional patterns derived from 15 O-water PET measurements ( Henriksen et al, 2021 ; Kilroy et al, 2014 ; Xu et al, 2010 ; Zhang et al, 2014 ). Furthermore, as a core node of the default mode network which high metabolic demand needed to maintain arousal ( Raichle et al, 2001 ), the posterior cingulate cortex has been shown to be one of the brain regions with the highest relative CBF ( Pfefferbaum et al, 2011 ).…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, the higher between-region CoV of relative GM CBF averaged across subjects (11.4%) over within-region CoV (2–4%) yielded excellent ICC values of VSASL for detecting normal variations of regional CBF ( Table 3 ). The higher relative CBF values in the occipital lobe (1.05), cerebellum (1.07), and posterior cingulate cortex (1.15) were consistent with the regional patterns derived from 15 O-water PET measurements ( Henriksen et al, 2021 ; Kilroy et al, 2014 ; Xu et al, 2010 ; Zhang et al, 2014 ). Furthermore, as a core node of the default mode network which high metabolic demand needed to maintain arousal ( Raichle et al, 2001 ), the posterior cingulate cortex has been shown to be one of the brain regions with the highest relative CBF ( Pfefferbaum et al, 2011 ).…”
Section: Discussionsupporting
confidence: 80%
“…For example, in fourteen healthy elderly subjects, Ishii et al found that MTL-OEF was ~7 units (%) lower than OEF in other cortical regions ( Ishii et al, 1996 ). Another three 15 O-PET studies reported that MTL-OEF was significantly lower than OEF in other cortical regions by 4–7 units ( Hatazawa et al, 1995 ; Henriksen et al, 2021 ; Yamaguchi et al, 1986 ). Ibaraki et al also showed lower MTL-OEF than OEF in other cortical regions in two 15 O-PET studies, although the authors did not perform statistical comparisons ( Ibaraki et al, 2008 ; Ibaraki et al, 2009 ).…”
Section: Discussionmentioning
confidence: 98%
“…30,49,50 If CMRO 2 is relatively stable, then it is apparent that a higher EtCO 2 would lead to a reduced OEF (because OEF is related to the ratio of CMRO 2 to CBF), which, in turn, would result in elevated Y v (Y v ≈ 1 À OEF). The crosssubject correlation between EtCO 2 and Y v can be similarly explained, as reports have shown a positive correlation between EtCO 2 and CBF across individuals, 51,52 while CMRO 2 values are relatively similar (or exhibits less variability compared with OEF or CBF) among subjects. 24 In this study, although we did not find any significant differences in Y v , intrasession CoV or intersession CoV values across the three scanners, we did observe that the GE TRUST had significantly higher ΔR 2 values than those of the other two scanners.…”
Section: Discussionmentioning
confidence: 79%
“…If CMRO 2 is relatively stable, then it is apparent that a higher EtCO 2 would lead to a reduced OEF (because OEF is related to the ratio of CMRO 2 to CBF), which, in turn, would result in elevated Y v ( Y v ≈ 1 − OEF). The cross‐subject correlation between EtCO 2 and Y v can be similarly explained, as reports have shown a positive correlation between EtCO 2 and CBF across individuals, 51,52 while CMRO 2 values are relatively similar (or exhibits less variability compared with OEF or CBF) among subjects 24 …”
Section: Discussionmentioning
confidence: 85%